Dual‐phase DC–DC buck converter with light‐load performance enhancement for portable applications. Issue 4 (1st April 2018) - Zhang, Shuyu; Zhao, Menglian; Wu, Xiaobo; Zhang, Haozhou
Abstract : In modern portable devices, except during short periods of busy time, application processors work at low‐power state most of the time to prolong battery life. Thus, high efficiency and low consumption are essential for their power management under light‐load conditions. This study presents a dual‐phase DC–DC buck converter with light‐load performance enhancement for power supply. As load decreases, the converter could transfer the adaptive‐on‐time‐based control strategy from pulse‐width modulation to pulse‐frequency modulation to enhance efficiency. An extra power‐save mode is introduced into design to minimise the power consumption at extremely light load. Besides, a novel current‐balance circuit with additional offset elimination block is implemented, which results in equal distribution of load current between phases over wide load range. Moreover, instead of a conventional high precision and fast response comparator, a simple comparator with self‐calibration is used in zero‐current switching circuit to reduce design complexity, as well as to improve light‐load efficiency. The converter is fabricated in 0.18‐μm Globalfoundry CMOS process. Experimental results show that91% peak efficiency and 6 µA standby quiescent current is achieved. With the aid of mode switching, current‐balance and zero‐current switching, the light‐load performance enhancement is verified by measurements.